Mineralogical and Geochemical Characteristics of Clays at Godean Hills, Yogyakarta – Indonesia (A Study Case at Gunung Patuk and Gunung Wungkal) - Yoellanice, Diory; Titisari, Anastasia Dewi; Setiawan, Nugroho Imam (Journal of Applied Geology, 2024)
Gunung Patuk and Gunung Wungkal are part of the Godean Hills in Yogyakarta, Indonesia. The Godean Hills are isolated hills consisting of a series of hills surrounded by the Young Merapi Volcanics Deposits. A previous study reported that Gunung Patuk and Gunung Wungkal are porphyry andesite – micro diorite intrusions. Both hills are igneous rock intrusion and are found almost perfect soil profiles from the source/parent rock to the A horizon. However, another previous study suggests that at Gunung Wungkal has occurred hydrothermal alteration process. There is still a debate over the genesis of clay in that area, therefore this research needs to be carried out to provide a comprehensive understanding of mineralogical and geochemical characteristics of the clays at that area. The results of petrographic identification on the source/parent rock sample indicate that the rock sample is classified as andesite rock. Meanwhile, the results of mineralogy identification using the X-Ray Diffraction (XRD) method show that almost all types of soil profiles contain illite, kaolinite, and smectite. The calculation results of CIW (Chemical Index Weathering) and CIA (Chemical Index Alteration) values based on geochemical data show that CIW and CIA values increase steadily as they approach the ground surface. Based on the presence of illite (indicates a product relating to the relatively high temperatures) in horizon A with high values of CIW and CIA, therefore it can be interpreted that clay minerals at Gunung Patuk and Gunung Wungkal were the product of superimpose of hydrothermal alteration and weathering processes.